Effects of a classwide teacher‐implemented program to promote preschooler compliance. Issue 3 (20th May 2014) - Beaulieu, Lauren; Hanley, Gregory P.
<x xml:space="preserve">Abstract</x> We used a multiple baseline design across skills to evaluate the effects of a program to teach a classroom of children to respond to their name and a group call (i.e., precursors) as well as to peer mediate these precursors to promote compliance with a variety of multistep instructions. Teachers taught these skills via classwide behavior skills training and a lottery‐based reward contingency. Results showed that precursors to compliance, peer mediation, and compliance increased as a function of classwide teaching, and the teachers found the procedures and their effects to be highly acceptable.